Creativity, Unique and Activities of Teachers, Students and Lecturers in Lockdown Virus Corona / Covid 19 - Amrozi Khamidi (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: In the midst of the policy of Merdeka Belajar era Menteri Nadiem Makarim, we are died with the coronavirus outbreak (Covid-19). The policy in place is to study at home. It's been more than two weeks of schooling we've had off, but the learning process of teaching continues through activities at home. Teachers teach from their own homes, students study in their homes. Home learning can use self-learning models, online learning, ICT-assisted learning, or other forms. Design/methodology/approach: Our research uses a type of qualitative research that explores data according to the facts that occur in the field with data collection methods through interviews, observations and documentation to obtain the results of research that occurs in schools and campuses during the coronavirus lockdown/ covid 19 Findings: The online learning process has brought creativity to students, students and teachers and lecturers both through school work and community service activities in order to jointly find solutions to the prevention of coronavirus/covid 19 outbreaks. For example students make masks for themselves and donated to the community, some make their own hand wash soap at home and there are community service activities by making hand wash sinks. Research limitations/implications: This research is conducted in the early phase of pandemic. The condition may change at the end of pandemic. Practical implications: We propose that educational institutions should be able to uncover lockdown during the covid-19 pandemic wisely. Find the right solution to solve these online learning problems with creativity and thoughtful solutions. Originality/value: This paper is original. Paper type: Research paper